Dominant-Negative TGF-β Receptor Enhances PSMA-Targeted Human CAR T Cell Proliferation And Augments Prostate Cancer Eradication - Kloss, Christopher C. (Mol Ther, 2018)
Cancer has an impressive ability to evolve multiple processes to evade therapies. While immunotherapies and vaccines have shown great promise, particularly in certain solid tumors such as prostate cancer, they have been met with resistance from tumors that use a multitude of mechanisms of immunosuppression to limit effectiveness. Prostate cancer, in particular, secretes transforming growth factor β (TGF-β) as a means to inhibit immunity while allowing for cancer progression. Blocking TGF-β signaling in T cells increases their ability to infiltrate, proliferate, and mediate antitumor responses in prostate cancer models. We tested whether the potency of chimeric antigen receptor (CAR) T cells directed to prostate-specific membrane antigen (PSMA) could be enhanced by the co-expression of a dominant-negative TGF-βRII (dnTGF-βRII). Upon expression of the dominant-negative TGF-βRII in CAR T cells, we observed increased proliferation of these lymphocytes, enhanced cytokine secretion, resistance to exhaustion, long-term in vivo persistence, and the induction of tumor eradication in aggressive human prostate cancer mouse models. Based on our observations, we initiated a phase I clinical trial to assess these CAR T cells as a novel approach for patients with relapsed and refractory metastatic prostate cancer (ClinicalTrials.gov: NCT03089203).